PECULIARITIES OF APPLICATION OF SPECIAL PRINCIPLES OF RELEASE FROM SERVING A SENTENCE FOR CRIMINAL OFFENCES (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the study of general and special principles of application of release from serving a sentence for persons who have committed criminal offences. The author also examines the problematic issues arising in connection with the application of such measures. It has been established that the release of a person from serving a sentence with probation on the basis of Art. 75 of the Criminal Code of Ukraine for committing criminal offenses may take place in the event of the person being sentenced to correctional labor, service restriction for military personnel, and restriction of liberty. At the same time, such a measure of a criminal law nature cannot be applied for the commission of certain criminal offenses (Part 1 of Art. 276 and Part 1 of Art. 281, Part 1, Part 3 of Art. 357 of the Criminal Code of Ukraine) due to the regulatory restriction of such a possibility. Also, when releasing a person who has committed a criminal offense from serving a sentence on the basis of Art. 75 of the Criminal Code of Ukraine, the court may impose on such a person an additional punishment in the form of a fine or deprivation of the right to hold certain positions or engage in certain activities. As for minors, they are provided with the possibility of being released from serving a sentence with probation for a period of 1 to 2 years in the event that a minor is convicted of a criminal offense and sentenced to imprisonment.
Keywords: release from serving a sentence; general principles; special principles; criminal offences; punishment; probation; sick leave; parole